Transmitting The Past In South Sulawesi: The Hikajat Sawitto And Other Bugis And Makasar Historical Works - Druce, Stephen C. (Penerbit Universiti Sains Malaysia (USM Press), 2016)
The central focus of this article is the hikajat Sawitto (hS), a 12-page typed text in the Latin script and Malay language constructed in the 1930s from mainly oral Bugis sources. The hS provides an important insight into how the past was transmitted in South Sulawesi and the relationship between orality and writing. Discussion of the hS is framed within this broader context and begins with an overview of Bugis and Makasar2 historical prose works, focusing mainly on the few longer written compositions dating from the 17th, to the 18th, 19th and 20th centuries, and the factors that influenced their creation. Central to the article is the argument that these written works are not representative of Bugis and Makasar historical sources and that orality played the primary role in transmitting the past. The article further demonstrates how the hS was constructed from independent sources and what these sources can reveal about the history of Sawitto. An annotated translation of the hS is presented within the article and the original appended.